Arthropoda yang Berasosiasi dengan Tanaman Refugia pada Pertanaman Padi di Desa Besur, Kabupaten Lamongan, Jawa Timur - Fathan Hadyan Rizki; Nina Maryana; Hermanu Triwidodo (Institut Pertanian Bogor, 2021)
Rice farmers in Besur Village planted four species of refugia plants around rice plants to enhance biological control as a part of Healthy Plant Management Program. These refugia plants were flowering plants i.e., Cosmos sulphureus, Helianthus annuus, Zinnia elegans, and Sesamum indicum. The objective of this research was to observe the Arthropods associating with these refugia plants. This research was conducted in December 2017 to March 2018 at Besur Village, Lamongan District, East Java Province. Samples were obtained from each refugia species by branches beating, sweep net, pitfall trap, and direct observation method in the vegetative, generative, and postharvest periods paddy plant. The results showed that Arthropods associated with refugia plants are mostly belong to the order of Diptera, Hymenoptera, and Araneae. Detritivore group was the most abundant in all periods. Analysis of the diversity and similarity of all refugia species showed moderate to high values with high similarities each other. Keywords: beneficial insect, flower, healthy plant management, integrated pest management, paddy field